Uncertainties in microseismic event location analysis - Święch, Eryk (Geology, Geophysics and Environment, 2015)
Microseismic monitoring is the observation technique of small earthquakes, called microseismic events, which occur in the ground as a result of human activities or industrial processes such as hydraulic fracturing. In this study author presents the application of different downhole array to investigate uncertainties in the estimated locations of microseismic event.